beta-Glucan protects against chronic nicotine-induced oxidative damage in rat kidney and bladder - ŞENER, GÖKSEL; ÇETİNEL, ŞULE (ELSEVIER SCIENCE BV, 2007)
In this study, we investigated the protective effect of P-glucan against nicotine induced oxidative damage in urinary bladder and kidney tissues. Wistar albino rats were injected i.p. with nicotine hydrogen bitartarate (0.6 mg/kg daily for 21 days) or saline. P-Glucan (50 mg/kg, p.o.) was administered alone or with nicotine injections for 21 days. After decapitation, the urinary bladder and kidney tissues were taken for the measurement of malondialdehyde (MDA) and glutathione (GSH) levels, and myeloperoxidase (MPO) activity. Tissue samples were also examined histologically. In serum samples NIDA, GSH, BUN, creatinine, TNF-alpha levels and LDH activity were analyzed. Chronic nicotine administration caused a significant decrease in GSH levels and increases in NIDA levels and MPO activity in kidney and bladder tissues, suggesting oxidative organ damage, which was also histologically verified. Furthermore, P-glucan restored the reduced GSH levels, while it significantly decreased NIDA levels and MPO activity. Renal function tests, LDH and TNF-alpha levels, which were increased significantly due to nicotine administration, were decreased with beta-glucan treatment. The present data suggest that beta-glucan supplementation effectively counteracts the chronic nicotine toxicity and attenuates oxidative damage of bladder and kidney tissues possibly by its antioxidant effects. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: beta-glucan; nicotine; kidney; bladder; oxidative damage; MYELOPEROXIDASE ACTIVITY; LIPID-PEROXIDATION; CYTOKINE RELEASE; INDUCED TOXICITY; CIGARETTE-SMOKE; MELATONIN; STRESS; BETA-1,3-GLUCAN; INFLAMMATION; GLUTATHIONE